Finite element evaluation of three methods of stable fixation of condyle base fractures - Jesus, G. P. de [UNESP]; Vaz, Luis Geraldo [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Passeri, L. A. [UNESP]; Oliveira, T. V. [UNESP]; Noritomi, P. Y. [UNESP]; Juergens, P. [UNESP] (Churchill Livingstone, 2014)
The surgical treatment of mandibular condyle fractures currently offers several possibilities for stable internal fixation. In this study, a finite element model evaluation was performed of three different methods for osteosynthesis of low subcondylar fractures: (1) two four-hole straight plates, (2) one seven-hole lambda plate, and (3) one four-hole trapezoidal plate. The finite element model evaluation considered a load applied to the first molar on the contralateral side to the fracture. Results showed that, although the three methods are capable of withstanding functional loading, the lambda plate displayed a more homogeneous stress distribution for both osteosynthesis material and bone and may be a better method when single-plate fixation is the option.
Keywords: finite element analysis; mandibular condyle; mechanical processes